2014
DOI: 10.1253/circj.cj-14-0500
|View full text |Cite
|
Sign up to set email alerts
|

Ulcer Healing After Peripheral Intervention

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp panied by an increase in renal diseases, and the incidence of peripheral arterial disease (PAD) among dialysis patients is also increasing. In Japan, 50% of CLI patients have endstage renal disease (ESRD). 7 Furthermore, populations are aging rapidly in advanced countries; in other words, disease duration is increasing among DM and ESRD patients, in turn, increasing the risk of triggering and advancing arterial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…38 A study by Kobayashi et al in 177 individuals found wound location most commonly at toe followed by Heel. 39,40 Heel and extensive wounds were found difficult to heal. 39,40 Further, delayed heel ulcer are directly linked to major amputation.…”
Section: Discussionmentioning
confidence: 99%
“…38 A study by Kobayashi et al in 177 individuals found wound location most commonly at toe followed by Heel. 39,40 Heel and extensive wounds were found difficult to heal. 39,40 Further, delayed heel ulcer are directly linked to major amputation.…”
Section: Discussionmentioning
confidence: 99%
“…Okazaki et al (25) published their results after surgical or endovascular revascularization of ischemic limbs: 64% ulcer healing at 12 months and their median ulcer healing time was 144 days. Azuma et al (26) published in 2014 a thorough review of the literature on ulcer healing after revascularization. Among the many studies reporting limb salvage, they found only 17 (0.1%) reporting data on wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Among the many studies reporting limb salvage, they found only 17 (0.1%) reporting data on wound healing. In these, 1-year wound healing rates vary between 47% and 87%, we calculated the weighted median healing time of them to be 186 days ranging from 64 to 267 days (26). wound healing is dependent on several factors including patient comorbidities and local ulcer factors as depth, size, localization, and presence of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction of soft tissue defects in the presence of chronic osteomyelitis remains difficult [11]. Even successful arterial reconstruction and free flap transfer does not necessarily guarantee the salvage of legs with extensive osteomyelitis [12], and adequate wound debridement and strict control of infection are prerequisites for the successful free flap insertion, prevention of infection recurrence, and subsequent amputation [10, 13].…”
Section: Case Presentationmentioning
confidence: 99%